Territorial shock: Toward a Theory of Change - Gertjan Dijkink (L'Espace Politique)
This article tries to explain territoriality as a social assemblage linked to a geographic base which is restructured during crucial (axial) periods in history. Since the last decades of the 20th century, frequent attempts have been made to understand ‘globalization’ by looking to earlier‘re-territorializations’ in history (particularly the emergence of territorial states in Europe at the end of the Middle-Ages). The dynamic model proposed by the author involves three territorial principles (control, closure and identity) that alternate in terms of active and passive at each transition to a new territorial epoch. This mechanism also casts some light on the great spiritual (religious) changes that seem to accompany territorial change and reveal its disturbing impact (like an earthquake) on contemporaries. According to this perspective we are now entering a period in which territorial solidarity (citizenship) is severely tested although a clear geography of power continues. New spiritual movements promote de-territorialization and individual resilience.